AIAA Infotech@Aerospace 2010 2010
DOI: 10.2514/6.2010-3504
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison and Evaluation of Real-Time Software Systems Modeling Languages

Abstract: A model-driven approach to real-time software systems development enables the conceptualization of software, fostering a more thorough understanding of its often complex architecture and behavior while promoting the documentation and analysis of concerns common to real-time embedded systems such as scheduling, resource allocation, and performance. Several modeling languages have been developed to assist in the model-driven software engineering effort for real-time systems, and these languages are beginning to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The UML profile for AADL is being adopted as a part of the MARTE profile. The strategy for combining the two provides a bridge to translate AADL models into MARTE, or vice-versa, the need should arise during a modeling effort 8 .…”
Section: Aadl and Their Behavior Annex: An Overviewmentioning
confidence: 99%
“…The UML profile for AADL is being adopted as a part of the MARTE profile. The strategy for combining the two provides a bridge to translate AADL models into MARTE, or vice-versa, the need should arise during a modeling effort 8 .…”
Section: Aadl and Their Behavior Annex: An Overviewmentioning
confidence: 99%
“…Based on these expressed needs and taking into account a study reported in [7], MARTE was found as a suitable modeling language to implement the ECOA metamodel. It provides facilities to annotate models with information required to perform specific analysis [2].…”
Section: Need For Modules Modelingmentioning
confidence: 99%
“…A comparison and evaluation of real-time modeling languages was addressed in [7] with respect to amongst other criteria the scope, the formalism, and the architectural coverage. Several real-time software system modeling languages were reviewed, namely the Architectural Analysis and Design Language (AADL) [9], the Unified Modeling Language (UML) [10], Systems Modeling Language (SysML) [11], [12], the Modeling and Analysis of Real-Time Embedded Systems (MARTE) UML profile [2], and the AADL for UML profile.…”
Section: Related Workmentioning
confidence: 99%
“…In this way, the proposed methodology in relation to the requirements elicitation is more expressive and simple to visualize. Moreover, AADL, UML, SySML and MARTE have certain limitations [30], that include the lack of abstractions for certain components like the operating system in real-time and the absence of behavior models (AADL); difficulties to handle a large amount of diagrams (UML and MARTE); the restriction to the utilization in the systems engineering domain only (SySML) and the complex underlying metamodel (MARTE). If necessary, the proposed methodology in this paper can be complemented with any of the mentioned modeling methodologies.…”
Section: Previous Workmentioning
confidence: 99%